Optimalisasi Jalur Tanggap Darurat di Institusi Pendidikan: Studi pada Gedung Jurusan Kesehatan Politeknik Negeri Jember - Puspitasari, Nilam; Aprilya, Nurina; Abdul Rauf, Muhammad (Poltekes Bhakti Pertiwi Husada, 2024)
Introduction: The safety of occupants in high-rise buildings is a primary concern, especially in Indonesia, which is prone to fires and earthquakes. The Health Department Building at Politeknik Negeri Jember faces challenges in meeting safety standards, such as insufficient directional signs, inadequate emergency lighting, and suboptimal assembly points. Research Objectives: To evaluate and optimize the emergency response routes in the Health Department Building of Politeknik Negeri Jember. Methods: The study utilized an observational method by directly examining the conditions of the emergency response routes in the Health Department Building. The data collected were analyzed and used to redesign the evacuation routes using SketchUp software. Results: The findings revealed that the evacuation routes did not meet safety standards, with deficiencies including inconspicuous directional signs, substandard emergency lighting, and poorly located assembly points. Recommendations included improving facilities, adjusting layouts, and adding safety signs to enhance evacuation efficiency and occupant safety. Conclusion: Optimizing evacuation routes is expected to improve the safety of building occupants. This study provides recommendations for better emergency response management, which are also applicable to other educational institutions.